Nano-liposome of thyme essential oil promotes growth performance, antioxidant and immune responses to aeromonad septicemia in Nile tilapia, Oreochromis niloticus, fingerlings - Yousefi, Morteza; Hoseini, Seyyed Morteza; Ghadamkheir, Maryam; Mahboub, Heba H.; Vatnikov, Yury Anatolyevich; Kulikov, Evgeny Vladimirovich; Sotnikova, Elena Dmitriyevna (Frontiers in Marine Science, 2023)
Nano-encapsulation protects essential oils and increases their efficiency, compared to bulk forms. Hence in the present study, four diets (328 g/kg crude protein and 4402 kcal/kg gross energy) containing 0 (CTL), 25 mg/kg (25TV), 50 mg/kg (50TV), and 100 mg/kg (100TV) thyme, Thymus vulgaris, essential oil nano-liposomes (TV-NP) were offered to Nile tilapia fingerlings (initial weight of 4.27 ± 0.05 g) at water temperature of 26.46 ± 0.43°C, followed by intraperitoneal infection by Aeromonas hydrophila. Three hundred and sixty healthy fish were stocked in 12 tanks (60 L), 30 fish per tank, with daily water renewal rate of 40%. Each diet was offered to three tanks for 70 days. The fish were sampled at the end of feeding period and 12 h after the bacterial challenge. Compared to CTL, 50TV and 100TV treatments exhibited significant elevations in growth rate (14-17%; P<0.001), intestinal activities of amylase (9-19%; P=0.004), lipase (13-26%; P<0.001), protease (20-23%; P=0.001), and post-challenge survival (26-27%; P=0.001). Plasma lysozyme (14-15% P<0.001) and complement (5.1-5.4%; P=0.004) activities significantly increased in 25TV and 50TV, but decreased (lysozyme: 19%, complement 5.9%) in 100TV before the challenge; however, all TV-NP treatments showed similar lysozyme and complement activities after the challenge that were higher than CTL. 50TV and 100TV treatments also showed a decrease in lipid peroxidation (23-26%; P<0.001) and highest glutathione peroxidase activity (17-18%; P=0.001) and pre-challenge superoxide dismutase (21%; P=0.046) and catalase (15-17%; P=0.001) activities. Expression of tumor necrosis factor-alpha (11-fold, P<0.001), inerleukin-1 beta (5-fold, P<0.001), and transforming growth factor-beta (31-fold; P=0.001) in head kidney significantly increased in 100TV before the challenge. After the challenge, the transcripts of the cytokines significantly increased in all treatments and the highest expressions were observed in 50TV and 100TV treatments (62-148-fold). In conclusion, dietary 50-100 mg/kg TV-NP can be considered as a new feed additive in tilapia culture, as it improves growth rate, antioxidant capacity, and disease resistance in the fish.